Conceito de identidade: contextos, traços e pertinências na vida organizacional - Lorda, Natalia Jauregui (2011)
The goal of this paper is to discuss the several notions of “organizational identity” by means of revising the recent literature, and thus outlining the history of the concept of identity in Psychology, Sociology and Organizational Studies. More specifically, we have analyzed how the concept of identity changed from modernity to post-modernity, and how the changes during this period of time affected the corporate world. For exploratory and illustrative purposes, we have carried out a qualitative research with employees of a major Brazilian organization in the financial industry, chosen due to the fact that it has just been through a merger with another organization of the segment. The research seeks to assess how the employees of two areas responsible for disseminating values perceive the organization‟s identity, and to verify if this perception can be read and interpreted by means of the concepts previously outlined. The research provided positive results revealing organizational identity concepts that are linked to the post-modern theories, which envision identity as a dynamic, fluid or liquid phenomenon.